MENGATASI KEJENUHAN SISWA KELAS II SEKOLAH DASAR - Zahara, Rosina; Mutia, Fahlila; Rahayu, Nora; Anggreini, Gita Sari (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
Successful learning is marked by the enthusiasm and enthusiasm of students in participating in the learning process. Another factor that supports the learning process is a learning atmosphere that is not boring and activities that make students happy and do not feel bored in learning. Saturation of learning is a mental condition of a person when experiencing extreme boredom and fatigue resulting in a feeling of lethargy, lack of enthusiasm or enthusiasm for activities. This study uses a descriptive qualitative approach. To obtain data the researcher conducted interviews, observation, documentation. High learning saturation results in low motivation for achievement in students. The consequences that arise because students experience boredom in learning are decreased achievement scores in learning or have low achievement in learning, skipping class, undisciplined, reluctant to learn, passive in class, busy in class, often leaving class, unable to answer questions, not doing homework etc. Although it must be admitted, boredom can be experienced by anyone. Therefore individuals must get an understanding and explanation of the consequences of learning boredom experienced by students.